The Issues Regarding Waqf Ownership of the Bukharan Emirate in Historical Sources - Ismatova, Nargiza (Researchparks Publishing, 2023)
The article analyzes information directly and indirectly related to the endowment issue in the historical works created in the Bukhara Emirate of the second half of the 19th century - the beginning of the 20th century.